‘How To Be A Good Parent’ Psychoeducation To Improve Parents' Understanding Of Permissive Parenting In “X” Elementary School In Surabaya City - Wahid, Sulhan; Noviekayati, IGAA (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study aims to improve parents' understanding of permissive parenting through a psychoeducation programme, which was conducted at SD “X” Surabaya City. Twenty participants attended the one-day ‘How to be a Good Parent’ programme, which included pre-test and post-test, discussion, and reflection. The intervention consisted of two sessions: ‘Getting to Know My Parenting’ and “Growing Up With My Child”. Pre- and post-test analyses using t-tests showed a significant increase (p<0.05) in participants' understanding of parenting. Seventeen participants had increased understanding